Comparative Analysis of Regenerants between Single and Naked Meristem (scalps) of Musa acuminata var. Berangan - Juli, N.A.; Khalid, Norzulaani (Malaysian Society for Molecular Biology and Biotechnology, 2002)
The regeneration capacity of banana meristem in vitro was compared between single meristem and scalp methods. Scalps were induced on p4 media containing MS (Murashige and Skoog, 1962) components supplemented with coconut water and high concentration of benzyl amino purine (BAP) (75Î¼M). The number of regenerated shoots produced from scalps was six-fold higher than that generated from single meristems. A comparison of the growth response upon gibberelic acid (GA3) treatment was made between plantlets derived from both methods to detect dwarf off-types. The difference in height and the number of leaves between plantlets from both sources was statistically insignificant. On the other hand, RAPD analysis using 40 random primers displayed approximately 26 variation in single meristem while naked meristem exhibited 74 variation.